ANALISIS VALUE CHAIN PADA RESTORAN HALAL DALAM ESTABLISHING HALAL VALUE CHAIN - Suyuti, Mufit; Yuniarti Hidayah Suyoso Putra; Meldona (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses Halal value chain analysis. The Halal value chain analysis method used in this research focuses on internal Halal restaurants which refers to Porter's Value Chain theory. Halal Value Chain analysis is divided into primary activities and secondary activities. This research uses a literature study method because the main aim of this research is to investigate and analyze the Value Chain in Halal Restaurants in Establishing a Halal Value Chain. The data used was taken from journals, news, and so on related to this research. Halal Value Chain, which refers to Porter's Value Chain theory, is considered to be able to analyze halal quality in halal restaurants because it focuses on restaurant internals, apart from increasing food safety for Muslim consumers. Restaurant owner awareness is very important for the protection of halal food. The regulatory framework needs to be improved to better support the halal industry.